3 - Academic Freedom and the Constriction of Democratic Space in Botswana: Reflections from an Academic-cum- Politician - Taolo Lucas, (Journal of Higher Education in Africa, 2011)
Academic freedom in Botswana is not institutionalized by law. It is only assumed in practice. In recent years however, the government of Botswana has shown a willingness and eagerness to use and exploit existing laws to stifle criticism and free speech. The enactment of such legislation as the Media Practitioners and the Intelligence and Security Act in their current form and the refusal to pass an open democracy law are clear indicators of a government that is hostile to a free flow of information. The timidity of both staff and students and their failure to engage both management and govern- ment over the erosion of their freedom serves as a fertile ground for more repression on students and staff in institutions of higher learning in the future. It is the argument of this article that as the legal environment, admin- istrative processes, and attitudes of the rulers point to a constriction of the democratic space in Botswana, academic freedom will be curtailed. There is thus an urgent need for students and academics to advocate the institution- alization of academic freedom and the opening up of democratic space. It is only when accountable, transparent and responsive governance structures are in place that academic freedom can flourish.